Объяснение:
Все эти уравнения решаются одинаково, раскрытием скобок.
1) (5x - 2)(x + 4) - x^2 = 28
5x^2 - 2x + 20x - 8 - x^2 - 28 = 0
4x^2 + 18x - 36 = 0
2x^2 + 9x - 18 = 0
D = 9^2 - 4*2(-18) = 81 + 144 = 225 = 15^2
x1 = (-9 - 15)/4 = -24/4 = -6
x2 = (-9 + 15)/4 = 6/4 = 1,5
2) (2x-3)(x-4) - x^2 = 60 - x
2x^2 - 3x - 8x + 12 - x^2 + x - 60 = 0
x^2 - 10x - 48 = 0
D/4 = 5^2 - 1(-48) = 25 + 48 = 73
x1 = 5 - √73; x2 = 5 + √73
3) 12x^2 - (2x-1)(x+6) = 70+13x
12x^2 - 2x^2 + x - 12x + 6 - 70 - 13x = 0
10x^2 - 24x - 64 = 0
5x^2 - 12x - 32 = 0
D/4 = 6^2 - 5(-32) = 36 + 160 = 196 = 14^2
x1 = (6 - 14)/5 = -8/5 = -1,6
x2 = (6 + 14)/5 = 20/5 = 4
4) 4x^2 - (2x-1)(x+5) = 19x - 21
4x^2 - 2x^2 + x - 10x + 5 - 19x + 21 = 0
2x^2 - 28x + 26 = 0
x^2 - 14x + 13 = 0
(x - 1)(x - 13) = 0
x1 = 1; x2 = 13
Объяснение:
1. 1) (Х+9) ²=х²+18х+81
2) (3а-8b) ²=9a²-48ab+64b²
3) (m-7) (m+7) =m²-49
4) (10b+6a) (10b-6a) =100b²-36a²
2. 1) c²-1=(c-1) *(c+1)
2) x²-4x+4=(x-2) ²=(x-2) *(x-2)
3) 25y²-4=(5y-2) *(5y+2)
4) 36a²-60ab+25b²=(6a-5b)²=
(6a-5b)(6a-5b)
3.(x+3)(x-3) -(x-4) ²=x²-9-(x²-8x+16) =
x²-9-x²+8x-16=8x-25
4.(5x-1)(x+2)+3(x+4)(x-4)=2(2x+3)²-8
5x²+10x-x-2+3*(x²-16) =2(4x²+12x+9) -8
5x²+9x-2+3x²-48=8x²+24x+18-8
8x²+9x-50-8x²-24x-10=0
-15x-60=0; 15x=-60; x=-4
5) (3a-1)²-(a+2)²=(3a-1-(a+2)) *(3a-1+(a+2)) =
(3a-1-a-2) *(3a-1+a+2) =(2a-3) *(4a+1)
{xy=12 {xy=12 {(4+y)y=12
(4+y)y=12
y²+4y-12=0
D=16-4*(-12)=16+48=64
y₁=(-4-8)/2=-12/2=-6 x₁=4+(-6)
x₁=-2
y₂=4/2=2 x₂=4+2
x₂=6
ответ: х₁=-2 у₁=-6
х₂=6 у₂=2
2) {x²-3y=22 {x²-3y=22 {(2-y)²-3y-22=0 {4-4y+y²-3y-22=0 {y²-7y-18=0
{x+y=2 {x=2-y {x=2-y {x=2-y {x=2-y
y²-7y-18=0
D=49-4*(-18)=49+72=121
y₁=(7-11)/2=-4/2=-2 x₁=2-(-2)
x₁=4
y₂=18/2=9 x₂=2-9
x₂=-7
ответ: х₁=4 у₁=-2
х₂=-7 у₂=9
3) {y-x=2 {y-2=x {y-2=x {y-2=x
{y²-4x=13 {y²-4(y-2)-13=0 {y²-4y+8-13=0 {y²-4y-5=0
y²-4y-5=0
D=16-4*(-5)=16+20=36
y₁=(4-6)/2=-2/2=-1 x₁=-1-2
x₁=-3
y₂=10/2=5 x₂=5-2
x₂=3
ответ: х₁=-3 у₁=-1
х₂=3 у₂=5